'It's something I believe in, but it's not something I understand': white teacher educators working towards antiracist pedagogy. Issue 1 (2nd January 2023) - Reinke, Luke T.; Miller, Erin; Glass, Tehia S.
ABSTRACT: In this manuscript, we (a racially diverse team of teacher educators) describe a study that reveals how five white faculty members in a large urban college of education experienced a two-day workshop on antiracism offered by a local antiracist coalition and the impact of the workshop in relation to their roles as teacher educators with a commitment to learning about and enacting antiracist pedagogies. Using qualitative methodologies including semi-structured, one-on-one interviews, we offer an underrepresented view of the tensions and possibilities of faculty learning to challenge whiteness in the academy by building antiracist pedagogies into their teacher education courses. In conclusion, we provide a series of recommendations to teacher educators who work in programmes committed to enacting antiracist pedagogies.